(untitled) (Purbanchal University Health Journal, 2025)
Introduction: Aceclofenac has rate-limiting dissolution steps, lower solubility and higher permeability physical properties. Different brand products of same drugs require analysis for their biopharmaceutical equivalence to ensure efficacy and their safety. Objective: This study aims to analyses biopharmaceutical and physicochemical equivalence of different trade of sustained release Aceclofenac tablets manufactured in Nepal. Method: A cross-sectional study with sustained release tablets of Aceclofenac from Eight different manufacturer were collected and analyzed for their biopharmaceutical and physicochemical properties through two standards and established methods. Descriptive statistics were calculated. Result: The weight variation of all brands ranged within the maximum limit of ±5% except brand H. Most of the brands had the recommended hardness (≥4Kg/cm2). The friability values of all products were within the recommended specification (≤1%). Assay conducted for all tablets revealed that they contain medicine ranging between 85-115% which indicate that all tablets pass the test for assay. The percentage drug release of all brand was in the range of 50 – 80% except brand E showed 63.88% drug release in 8th hour. The brand A, B and H followed pappes release model of kinetic and brand C followed zero order kinetic whereas brand D and G followed first order kinetic model and brand E & F followed Higuchi model. Conclusion: All brands except one were interchangeable in terms of biopharmaceutical equivalence and sustained release formulation. Further, more in-vivo bioequivalent studies should be conducted to correlate the findings.